The Effectiveness of The Spelling Method to Upgrade The Writing Skill of Students - Aniatul Khasanah; Agus Nu'man (STAI Nurul Huda Kapongan Situbondo, 2022)
Writing is one of the language skill used in indirect communication, the writing skill is not acquired naturally, but must go through a process of learning and practice. This research is a quantitative research in an experimental design style. The type of research used in this research is a pre-experimental design in the form of a one-group pre-test design. The research data was obtained by conducting a written pre-test and a post-test on the subject “Our School Diaries”. The results of calculating the t-test at a significant level of 0.05 obtained a calculated value of 0.174. Therefore, it can be concluded that the effective use of a dictation method to improve the writing skill of first-grade students from Nour El-Huda Intermediate School for Girls, Flean Kavogan Situbondo.